Feasibility of Telementoring as an Intraoperative Time-out Tool during Laparoscopic Cholecystectomy for Prevention of Biliovascular Injuries - Laudari, Uttam; Pradhan, Rosi; Shrestha, Dibesh; Bhandari, Shreya; Thapa, Prabin Bikram (Journal of Nepal Health Research Council, 2023)
Laparoscopic cholecystectomy is commonly performed procedure for gallbladder diseases. Biliovascular injuries are well known complications and various standard and safe strategies have been developed for safe cholecystectomy. Intraoperative time out is one of the strategies where two or more surgeons stop during surgery before dividing any structure in Calot’s triangle. COVID-19 pandemic has expanded the horizon of telesurgery, teleconsultation, use of artificial intelligence and robotics in surgical training and execution. Easily available mobile applications like Facebook messenger, WhatsApp and Viber can be used for intraoperative time-out during difficult cholecystectomy with expert surgeon outside the vicinity of theatre. Such tools are cost effective and definitely boost the confidence of surgeons during surgery in case of any complexity, or help in stopping the procedure and in timely referral.Keywords: Cholecystectomy; laparoscopy; telementoring.